Perceptual plasticity in the peripheral visual field of older adults - Blighe, Alan (2014)
Perceptual learning is an important mechanism in the human visual system, and can lead to long-lasting improvements across a broad range of perceptual tasks. In this study we demonstrated how perceptual learning can be applied to improve word recognition in the peripheral visual field of a sample of older individuals. We have shown that improvements in thresholds can be equalised across age, simply by increasing the number of training sessions available to older observers.